Implementasi Model Contectual Teaching And Learning Untuk Meningkatkan Pemahaman Siswa Tentang Konsep Mengurutkan Bilangan Pada Mata Pelajaran Matematika Di Kelas IV SDN Montor 2 - Enah Siti Hasanah (Universitas Mathla'ul Anwar Banten, 2017)
The use of methods contectual teaching and learning method is expected to increase comprehension and student activity in teaching and learning process of mathematics subject at class IV. This reasearch used action research In two cycles. It cycles consists of four phases: design, activitiesand observations, watching, and refision. These results showed that the student convrehension and achievement are increased from pre-cycle, the first cycle till the second cycle. Teh result of student learning at pre siklus pasess is average 46.6 with completeness (40%), the first cycle of the average 62 with completeness (73.3%), and the second cycle the average 79 with completeness (100%). It shows that learning by using this method can be a positive influence on the comprehension, achievement and motivation of student at class IV SD Negeri Montor Pagelaran District, Pandeglang regency..